TI_GERICHTE 12.2018.95 vom 30. Januar 2020 , Banca - responsabilità per chiusura di operazioni su divise OTC - vizio di volontà - TI Tribunale d'appello (2020)
Banca - responsabilità per chiusura di operazioni su divise OTC - vizio di volontà